New Reactivity of Masked Isocyanates with Organometallic Reagents - Mohamed, Alshimaa Mohamed Ahmed (Université d'Ottawa | University of Ottawa, 2024)
The research presented in this thesis centers around the stoichiometric addition of organometallic reagents, particularly Grignard reagents, to heteroatom-substituted isocyanates to provide access to hydroxamates and hydrazides via C-C bond forming reaction with masked O-isocyanates and N-isocyanates, respectively. It is demonstrated that Grignard reagents can effectively generate free O- and N- isocyanates in situ from blocked precursors, enabling high-yielding addition reactions, provided that diorganomagnesium reagents are used. The investigation explores the formation of a relatively stable five-membered chelate as a key aspect in the addition of Grignard reagents to masked heteroatom-substituted isocyanates. This chelate controls the release of the reactive isocyanate, hence mitigating uncontrolled reactivity including oligomerization of isocyanates and/or rearrangement. Heating at reflux in THF is required to overcome the stability of the chelate formed upon deprotonation. Precise adjustment of the nature and coordination environment of the isocyanate/metal complex controls the release of the reactive isocyanate in situ, minimizing side reactions and enhancing the desired activity.
Keywords: Isocyanates; blocked isocyanates; masked isocyanates; O-isocyanates; N-isocyanates; heteroatom-substituted isocyanates